PRICES AND TESTIMONIALS IN DECISIONS MAKING TO USE SERVICES - Andri Tri Nugroho; Odang Kusmayadi (Jurnal Riset Bisnis dan Manajemen, 2021)
This research aims to determine customer perceptions about prices, testimonials and service user decisions at PT. Kampung Marketerindo Berdaya. The population were about 218 with the sample of 118 customers by an accidental sampling technique. while the data analysis is path analysis. In general, the results of this research indicated that price is in the good category as well as testimonials and service user decisions. The results of T Test showed that the prices partially has a significant effect on decision making for using services. Morever, testimonals partially has a significant effect on the decision to use services and the result of F test showed that the prices and testimonials simultaneously have a significant effect on the decision making to use services.